Market Reactions on Corporate Actions in Growing and Nongrowing Energy Consuming Companies - Nurwulandari, Andini; Hasanudin, Hasanudin; Melati, Melati (International Journal of Energy Economics and Policy, 2021)
This paper aims to analyze the market reactions on corporate actions in the form of split-up, reverse split, right issue, and mergers and acquisitions in growing and non-growing energy consuming companies in Indonesia. The market reaction is analyzed based on stock price, trading volume, and abnormal returns movements using paired sample t-tests from the results of the event study for five days before and after corporate actions in the form of split-up, reverse split, right issue, and mergers and acquisitions. The results showed that stock prices reacted positively on the split-up in growing energy consuming companies, while in non-growing energy consuming companies, stock prices did not react significantly. However, the abnormal returns of growing and non-growing energy consuming companies both showed a negative movement, while the trading volumes did not react significantly. This paper specifically analyzes the market reaction on corporate actions in growing and non-growing energy consuming companies to provide interesting insights about the different reactions given by the market to corporate actions carried out by the companies with different growth categories. Keywords: Market reaction, corporate action, split-up, reverse split, right issue, merger and acquisition JEL Classifications: D81, P48, Q35, Q42 DOI: https://doi.org/10.32479/ijeep.10737